Summary: Texts at Play. The Ludic Aspect of Karen Blixen’s Writings - Steponavičiūtė, Ieva (Scandinavistica Vilnensis, 2011)
The monograph is a discussion of Karen Blixen’s texts in the light of ‘play theory.’ By investigating the functions of various topoi of play and games, and tracing some of Blixen’s most common playful strategies, it suggests that play is the dominant principle of Blixen’s textual universe which otherwise seems to defy generalisation. Viewing play as a by and large social phenomenon, the study contributes to deconstructing the image of Blixen as a high brow, elitist author. Instead, the reader is invited to approach her texts as playgrounds of generous interaction, which one can enter from many interesting angles – in the true spirit of play.The monograph is Indexed in Web of Science Core Collection.
Keywords: Karen Blixen; play theory; modern Danish literature; Ieva Steponavičiūtė